Volatilitas USD/IDR di Tengah Ketidakpastian Global: Dampak Perang Dagang, Harga Komoditas, dan Kebijakan Bank Indonesia (Analisis GARCH-X Periode 2024–2026) - R Adisetiawan (Universitas Batanghari Jambi, 2026)
This study analyzes the volatility of the USD/IDR exchange rate and the impact of external risks, namely trade war and commodity prices, as well as the role of Bank Indonesia’s (BI) monetary policy during the period from October 20, 2024, to June 18, 2026. Using GARCH(1,1) and GARCH-X models on daily data, the research aims to identify the determinants of rupiah volatility amid global uncertainty. The estimation results reveal that USD/IDR volatility is highly persistent, with α + β values ranging from 0.93 to 0.96. The trade war (19% reciprocal tariffs) and rising commodity prices (Brent crude oil) have a positive and significant effect on increasing volatility. In contrast, successive BI Rate hikes up to 5.50% effectively reduce volatility (negative and significant coefficient). The GARCH-X model outperforms the standard GARCH in capturing external factors. These findings indicate that global uncertainties stemming from the trade war and commodity shocks are the primary drivers of rupiah volatility, while BI’s monetary policy response plays a crucial role in maintaining exchange rate stability. This study offers policy implications for strengthening monetary and structural policy coordination in facing external risks.